Rice response to cadmium bioremediation using sorghum and mycorrhiza - HARSONO, PUJI; HASANAH, NUR AZIZAH USWATUN; PURWANTO, EDI; SAMANHUDI, SAMANHUDI (Smujo International, 2025)
Abstract. Harsono P, Hasanah NAU, Purwanto E, Samanhudi. 2025. Rice response to cadmium bioremediation using sorghum and mycorrhiza. Asian J Agric 9: 522-532. Cadmium (Cd) contamination at 2.9 mg kg-¹ in paddy soils reduces rice productivity and threatens food safety. This study aimed to evaluate the effectiveness of sorghum (Sorghum bicolor) phytoremediation combined with Arbuscular Mycorrhizal Fungi (AMF) in improving rice growth under mild Cd contamination. A factorial randomized complete block design with two cropping systems (seed vs. ratoon, where the same crop is re-grown from the stubble or roots of the first crop) and seven remediation treatments (control; three sorghum varieties (Super 1, Samurai 1, Kawali) combine with/without 10 g AMF plot-¹) was applied in 42 plots (3×4 m). Rice cv. IR 64 was transplanted 30 days after remediation. Significant interactions (p<0.05) between cropping system and remediation treatment occurred for plant height and leaf area. The Kawali + AMF treatment produced the most significant gains relative to the control: plant height +7.7%, leaf area +207%, chlorophyll +236% and total dry biomass +152%, while extending the vegetative phase by 23%. Improvements were consistent across sorghum seed and sorghum ratoon systems, indicating that remediation benefits persist beyond the first harvest. Ratoon sorghum-maintained remediation benefits, with 7-10% taller plants and 8% greater leaf area than the control, despite slightly reduced canopy size compared with seed sorghum; all sorghum treatments delayed flowering by 11 days, indicating reduced Cd stress. High-biomass sorghum, especially Kawali, combined with AMF, enhances rice growth and physiology while stabilizing Cd, providing a scalable remediation strategy for sustainable rice production in Cd-contaminated tropical agroecosystems.